Designing Project Overhead Cost Attribution Calculation Module to Enhance Capital Expenditure Control (Case Study: PT G) - Ide Dia Selly; Machmudin Eka Prasetya (E-Jurnal Akuntansi, 2025)
Effective capital expenditure (capex) management in fixed asset investments, such as natural gas infrastructure projects, is essential to ensure investment feasibility. A component of capex is project overhead cost, which represent indirect expenses not directly linked to specific products or services and tend to increase as construction projects progress. This research addresses challenges faced by PT G, a national energy company, in allocating project overhead cost to ongoing projects using the SAP ERP system. The system only supports proportional cost allocation and lacks an integrated calculation method. Consequently, PT G relies on spreadsheets to manually calculate cost’s proportional allocations, based on project progress data from its project management information system (PMIS). This disconnected process results in redundancy, inadequate control over capital expenditure, and introduces risks such as human error, inconsistent results across users, and budget overruns. The aim of this study is to design an integrated construction overhead cost allocation module that utilizes real-time project progress data within PT G’s web-based project management system. The module is developed using the Object-Oriented Analysis and Design (OOAD) approach to ensure structured documentation and scalability. The findings show that the proposed module improves capex control by automating calculations, providing up-to-date information on realized spending and remaining budget limits, and enhancing data reliability and accountability through features such as activity logs and calculation logs. This integration reduces dependency on manual processes, streamlines workflows, and supports more accurate, transparent, and efficient financial management in infrastructure projects.